2015
DOI: 10.1103/physreva.92.042324
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional quantum walk under artificial magnetic field

Abstract: We introduce the Peierls substitution to a two-dimensional discrete-time quantum walk on a square lattice to examine the spreading dynamics and the coin-position entanglement in the presence of an artificial gauge field. We use the ratio of the magnetic flux through the unit cell to the flux quantum as a control parameter. For a given flux ratio, we obtain faster spreading for a small number of steps and the walker tends to be highly localized around the origin. Moreover, the spreading of the walk can be suppr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…Previous work on DTQWs coupled to electric or magnetic fields [26,27,33] have shown that walks with field values which are rational multiples of 2π ('rational fields') follow very peculiar dynamics. Fig.…”
Section: Simulations Outside the Continuous Limitmentioning
confidence: 99%
“…Previous work on DTQWs coupled to electric or magnetic fields [26,27,33] have shown that walks with field values which are rational multiples of 2π ('rational fields') follow very peculiar dynamics. Fig.…”
Section: Simulations Outside the Continuous Limitmentioning
confidence: 99%
“…For more general space dependent coins there would also be x-dependent coefficients. The first form in (37) is often used in the (theoretical or experimental) construction of walks, and is called a shift-coin decomposition. It is a product of two kinds of operations: On the one hand, the "coin" operations are just the localized unitary operators.…”
Section: Walks Shifts and Coinsmentioning
confidence: 99%
“…where P is a constant projection, which in the second equality has been taken as |1 1|. This special case suffices, because we allow products, and by conjugation with a constant coin we can include also shifts with P = |φ φ|, or like the first factor in (37). A walk will be called decomposable, if it can be written as a finite product…”
Section: Walks Shifts and Coinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, DTQWs on square lattices under artificial magnetic fields have been considered [48]. An artificial or synthetic magnetic field can be simulated as follows [49]: instead of using charged particles in an actual magnetic field, one typically uses neutral particles upon which the effects of a fictitious magnetic field are imposed, e.g.…”
Section: Introductionmentioning
confidence: 99%